SPORULATION OF CLOSTRIDIUM BOTULINUM II. : Effect of Arginine and its Degradation Products on Sporulation in a Synthetic Medium - Perkins, William E. (1962)
Perkins, William E. (National Canners Association Research Laboratory, Berkeley, Calif.) and Kiyoshi Tsuji. Sporulation of Clostridium botulinum. II. Effect of arginine and its degradation products on sporulation in a synthetic medium. J. Bacteriol. 84:86–94. 1962.—A synthetic medium which supports spore germination, vegetative cell multiplication, toxin production, and sporulation of Clostridium botulinum strain 62A is described. Arginine has been shown to play an important role in sporulation. Experiments involving the substitution of citrulline and ornithine for arginine, together with amino acid analyses of culture supernatant fluids and cells, indicate that most of the arginine is broken down by a dihydrolase enzyme system through citrulline to ornithine. The second step in this reaction series, the degradation of citrulline, appears to be essential to sporulation. The absence of citrulline or ornithine in either growing cells or spores suggests that another product of the arginine dihydrolase system, adenosine triphosphate, may be responsible for the observed stimulation of sporulation.